TIME AND DIRECTION EFFECT OF BORON (B) AND SILICON (Si) APPLICATION ON OIL PALM (Elaeis guineensis) THROUGH LEAVES - Ageng Kaloko (AGROLAND: The Agricultural Sciences Journal, 2017)
This study was aimed to obtain the time and the effective way of giving B and Si for reducing the effects of drought. It had been implemented in Bendosari village, Madurejo village, Prambanan sub-district, Sleman regency. The study used 3x3 +1 factorial complete randomized block design (RAKL) with with 3 blocks as replicates. The first factor was the time of fertilization, the second factor was way of fertilization and added one control (control) without fertilization treatment. The data obtained were analyzed using the Varian Analysis (ANOVA) at the 5% level and continued by the smallest real difference test (LSD) and orthogonal contrast if the variance analysis showed a significant difference between treatments. The results showed that there was no interaction effect between time and direction of B and Si fertilization through leaves on all observed variables of oil palm seedlings exposed to drought stress.